Altman Z-Score Dan Springate: Metode Komparasi Dalam Memprediksi Kemungkinan Kebangkrutan Suatu Perusahaan - Risa Wahyuni EDT; Hafizia Seriska (Akuntabilitas, 2022)
Bankruptcy can be experienced by every company that has a decline in the value of profits from year to year. Because Indonesia was hit by COVID-19 in the past, this study will predict company bankruptcy using the Altman Z-Score and Springate methods. In addition, this study was conducted to determine the most accurate bankruptcy prediction method in predicting infrastructure, utility and transportation sector companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling technique with a total sample of 23 companies. The data were analyzed using the calculation of the level of accuracy and type of error from each bankruptcy prediction model, to predict companies experiencing potential bankruptcy. The results of this study indicate that the Z-Score method is the most accurate method. Therefore, it can be concluded that the Altman Z-Score method is more accurate in calculating bankruptcy predictions than the Springate method.